Quasi-Dynamic Homogenization of Geometrically Simple Dielectric Composites - Qi, Jiaran; Kettunen, Henrik; Wallén, Henrik; Sihvola, Ari (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The frequency dependence of the effective permittivities of simple dielectric composites is evaluated by different quasidynamic homogenization methods. Three retrieval approaches based on the scattering parameters are proposed for dielectric materials. A compensation method for the conventional Nicolson-Ross-Weir (NRW) retrieval is applied to eliminate the Fabry- Pérot (FP) resonances and their distortions of the retrieval results. All these quasi-dynamic homogenization methods are then evaluated by comparing the corresponding retrieval results against one another. Finally, by comparing these retrieval results with the static Lord Rayleigh prediction, the limitation of the quasi-static approximation for such composites is considered.